(untitled) - Bethel, Dayle M. (New York, 1973)
Upon reaching Japan, Buddhism, which was founded in India two thousand years ago, collided with an island civilization with its own firmly entrenched cultural and even religious infrastructure. The result, as the Japanese embraced this new, foreign-born religion, was a centuries long "chemical reaction" between religion and culture. This book, written by one of Japan's most outstanding scholars on Buddhism, traces that journey from the beginning through our own time. Japanese Buddhism examines how the religion shaped the people-with their own rich history-even as the people shaped the religion, with the result that Japanese Buddhism is unique in the world today. Delving deeply into the interplay between Buddhism and Japanese poetry, literature and even politics, this book is an invaluable addition to our understanding of Japan, Buddhism and the complex relationship between the two.
Keywords: Education; Philosophy